Numerical simulation of a helium plasma–material interaction experiment in GyM linear device through SOLPS-ITER and ERO2.0 codes - F. Mombelli; G. Alberti; E. Tonello; C. Tuccari; A. Uccello; C. Baumann; X. Bonnin; J. Romazanov; M. Passoni; the GyM team (Nuclear Fusion)
In this paper, a numerical investigation of plasma–material interaction-relevant helium plasma experimental discharges in GyM linear device is presented, in which SOLPS-ITER and ERO2.0 codes are coupled for plasma background generation and material erosion investigation respectively, with the aim to support the interpretation and complement the available experimental dataset. On the plasma side, simulated profiles are validated against experimental data to provide a realistic plasma background, and the role of He metastable states is assessed for the first time in SOLPS simulations. On the material side, the erosion and deposition effects due to the introduction of the sample-holder in the simulation volume are investigated, now considering also the real stainless steel composition as wall material.